2011
DOI: 10.1039/c1ob06231j
|View full text |Cite
|
Sign up to set email alerts
|

C3-triiodocyclotriveratrylene as a key intermediate to fluorescent probes: application to selective choline recognition

Abstract: A new strategy to obtain fluorescent cyclotriveratrylene (CTV) probes is proposed. The key intermediate, a triiodo CTV, is prepared in 3 steps with 47% overall yield. The whole synthesis requires only one purification step. The potential of this triiodo CTV as an intermediate is illustrated through the synthesis of a fluorescent phosphorylated probe that is able to bind choline and acetylcholine in pseudo-physiological conditions, with selectivity towards choline. As a consequence, this intermediate should all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…As shown in Scheme , the synthesis of cyclotris(2‐mercaptomethyl)phenolene 1 H 6 started from the known triiodo‐CTB derivative 3 , which was obtained in four steps from 3‐hydroxybenzoic acid in 23 % overall yield. Halogen/metal exchange was carried out by the reaction of 3 with n BuLi at –78 °C, as reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme , the synthesis of cyclotris(2‐mercaptomethyl)phenolene 1 H 6 started from the known triiodo‐CTB derivative 3 , which was obtained in four steps from 3‐hydroxybenzoic acid in 23 % overall yield. Halogen/metal exchange was carried out by the reaction of 3 with n BuLi at –78 °C, as reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Other solvents and reagents were used as received. Compounds 3 and 4 [4c] were synthesized according to the literature. Deuteriated bases were obtained by dissolution of commercial bases in D 2 O followed by solvent evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the method developed by Gosse, [13] NaBH 4 was used to reduce propyl or butyl ester intermediate without deiodination instead of diisobutylaluminum hydride, which was used at -80°C. Treatment of 2a and 2b with P 2 O 5 and Et 2 O under reflux gave the cyclotribenzylene compounds 3a and 3b, which could be purified by recrystallization from CHCl 3 / hexane.…”
Section: Synthesismentioning
confidence: 99%
“…Further study showed that the more reactive indolylphosphane ligand was required. Gosse [13] reported an efficient route to synthesize the same CTV-I 3 starting from 3-hydroxy-4-iodobenzoic acid in three steps with 47 % overall yield. Collet reported the synthesis of CTV-I 3 in 1995.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation